Supplementation of arachidonic acid rich oil in European sea bass juveniles (Dicentrarchus labrax) diets: Effects on leucocytes and plasma fatty acid profiles, selected immune parameters and circulating prostaglandins levels. Issue 64 (May 2017) - Torrecillas, S.; Román, L.; Rivero-Ramírez, F.; Caballero, M.J.; Pascual, C.; Robaina, L.; Izquierdo, M.S.; Acosta, F.; Montero, D.
Abstract: The main objective of this study was to assess the effects of graded levels of dietary arachidonic acid (ARA), supplemented from alternative sources, on fatty acid composition of plasma and head kidney leucocytes of European sea bass ( Dicentrarchus labrax ). For that purpose, sea bass juveniles were fed four diets containing graded levels of ARA as follows: 0.5% (ARA0.5), 1% (ARA1), 2% (ARA2) and 4% (ARA4) during 60 days. At the end of the feeding trial fatty acid profiles of plasma and head kidney leucocytes were analyzed. Besides, plasma prostaglandins levels, head kidney leucocytes respiratory burst activity; peroxidase activity and phagocytic index were assayed. Reducing dietary ARA levels below 1% markedly reduced European sea bass growth performance. However, fish fed diet ARA0.5 tried to compensate this dietary ARA deficiency by a selective deposition of ARA on plasma and head kidney leucocytes, reaching similar levels to those fish fed diet ARA1 after 60 days of feeding. Nevertheless, head kidney phagocytic capacity was reduced as dietary ARA content in relation not only to variations on membrane composition but also to changes on fish basal prostaglandins levels. Results obtained demonstrated the importance to supply the necessary quantity n-6 LC-PUFA, and not only n-3 LC-PUFA levels, in European sea bass diets, in relation to not only growth performance but also immune system function. Highlights: Dietary ARA levels below 1% of total fatty acids limits European sea bass growth performance. Deficient dietary ARA supplementation compromises European sea bass head kidney leucocytes phagocytic activity. Dietary ARA levels conditions circulating prostaglandins levels. Fish fed insufficient dietary ARA compensates this deficiency by a selective deposition of ARA. Dietary n-6 LC-PUFA is determinant to obtain a proper European sea bass immune system function.